Analysis of Borax Content in Meatballs that are Sold in The Karang Jangu Environment - Bidarita Widiati; Sri Wahyuningsih (Hydrogen: Jurnal Kependidikan Kimia, 2023)
Meatballs are one of the foods that are popular with various groups in Indonesia. Borax is a prohibited substance used as a food additive. Borax is commonly used in soldering, glassmaking, porcelain and wood preservatives. The use of borax in crackers aims to increase the elasticity of the meatballs. The purpose of this study was to detect the presence of borax in meatball samples.This type of research is descriptive, the method used is a qualitative method. Meatball samples were taken from meatball traders who sold them in the Karang Jangu area, Meatball samples were taken from meatball traders who sold them in the Karang Jangu area and examined using tumeric paper, tumeric paper (curcumin paper) is filter paper that is dipped in turmeric solution and dried, after that the sample that has been diluted and homogenized is dripped onto the tumeric paper. Based on the results of the study of the five meatball samples that were examined qualitatively using tumeric paper, negative results were obtained or did not contain borax, this was made clear by the absence of a color change on the tumeric paper. It is hoped that future researchers can use other methods. which can detect the presence and levels of borax in meatballs.